(untitled) (Fiep Bulletin - online, 2011)
Dysmenorrhea, which means difficult or uncomfortable menstruation, affects more than 50% of women. Besides the pain, several symptoms follow it, such as vomit, nauseas, headaches, mastalgia, among others. This disturb is related to the growth in the production of prostaglandin on the first days of the menstrual period. These symptoms disable women to perform their daily activities. This research consists of an epidemiological study and aimed the female students of the physiotherapy course of a college in Cascavel – PR. An interview-like questionnaire, containing 19 questions related to dysmenorrhea was applied to the participants. In the results of the research, 87% reported incidence of dysmenorrhea in the family, 39% were between 6 and 8 in a scale of 0 to 10, 33% had an increase of pain along the time. The main points of pain reported in the research were on the abdominal region with 36% and on the lumbar region 36%, as for the practice of physical exercises, 83% of the interviewees didn’t practice any kind of exercise and 93% didn’t make use of tobacco. As for the daily living activities, 63% of the interviewees had to interrupt some activities due to pain related to menstruation. Compared to the literature, the incidence of dysmenorrhea cases were elevated and its discomfort hinders women, most of the time, to have a normal daily life, forcing them to interrupt their daily activities. Several forms of physiotherapeutic treatment are indicated and are efficient, but, it is suggested a higher number of research related to the treatment of this disturb, because it is very common and aggravating among women.